The Effect of Principal Leadership, Ethos, and Work Climate on Educator Performance MAN District of Sumedang - Riyanti, Triska; Hidayatulloh, Rochmat; Hidayat, Wahyu (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
Education is seen as a valuable investment in improving the quality of human resources and building a nation. The research focuses on the MAN Se-Kab district of Sumedang to analyze the leadership of the head of the school, the work ethos, the working climate, and the performance of the educators. Quantitative survey methods are used with data collection using lifts. Data analysis includes validity, reliability, classical assumption tests, double linear regression, and hypothesis tests. Research at MAN Se-Kab district Sumedang found that the leadership of the head of school, the work ethos, and the working climate were rated